Acceptability of Adaptations for Struggling Writers: A National Survey With Primary-Grade Teachers. (February 2016) - Graham, Steve; Harris, Karen R.; Bartlett, Brendan J.; Popadopoulou, Eleni; Santoro, Julia
One hundred twenty-five primary-grade teachers randomly selected from across the United States indicated how frequently they made 20 instructional adaptations for the struggling writers in their classroom. The measure of frequency ranged from never, several times a year, monthly, weekly, several times a week, and daily. Using a 6-point Likert-type scale, they also rated the acceptability of each of the 20 adaptations on five dimensions: suitability, effectiveness, negative effects, time to apply, and implementation know-how. Teachers reported making 13 different adaptations monthly or more often. The most common adaptations were extra encouragement and extra time to complete writing assignments, whereas the least common adaptations involved technology or dictation. Teachers viewed all of the adaptations as acceptable, and their views on acceptability made a unique and statistically significant contribution to predicting reported use of adaptations after variance due to student and other teacher variables was first controlled.